Does abuse depend on gender? Men as a victim of women’s violence - Płonka, Joanna (Journal of Gender and Power, 2020)
The aim of this article is an attempt to reflect on what violence is and what effects it can cause. The conventional wisdom has been that women are victims and men are perpetrators of violence and abuse. Social schemes describe women as fragile and vulnerable. However, women can be equally aggressive, dominating and use violence. Each year acts of violence against men increase and it is very important to be aware of this phenomenon. Usually men hide the fact of being abused out of fear of public stigma, felling bashful, being laughed or losing respect of their family. This paper aims to show how important this problem is and explore new ideas and possible solutions for victims of violence, as well as to improve preventive measures for abused men.